Analisis Siyasah Tanfidziyah Terhadap Implementasi Undang-Undang No 40 Tahun 2007 Tentang Perseroan Terbatas - Nisak, Siti Marhumatun; Faizal, Liky; Latua, Abidin (Legal Standing : Jurnal Ilmu Hukum, 2025)
Limited liability companies operate within the fabric of society and, therefore, their presence should ideally generate mutual benefits for both the corporation and the surrounding community. In pursuit of this objective, Article 74(1) of Law No. 40 of 2007 on Limited Liability Companies mandates that companies engaged in sectors related to natural resources are obligated to fulfill their social and environmental responsibilities. However, in practice, the implementation of this law is often limited to a formal compliance effort, lacking substantive action to achieve its intended purpose. Such responsibilities should be carried out earnestly to ensure that the intended social and environmental outcomes are effectively realized and not rendered ineffective or meaningless. The implementation of social responsibility in Law Number 40 of 2007 is a government effort to improve the standard of living of the community with regulations that should be implemented by the limited liability company. With data collection techniques through field research. Islamic law regulates between rights and obligations for the welfare of humanity with the existence of Fiqh siyasah tanfidziyyah, it can ensure that the policies implemented by limited liability companies and the government are truly appropriatein order to achieve the welfare of society.